2022
DOI: 10.1186/s12885-022-09838-0
|View full text |Cite
|
Sign up to set email alerts
|

The miR-199a-5p/PD-L1 axis regulates cell proliferation, migration and invasion in follicular thyroid carcinoma

Abstract: Background Follicular thyroid carcinoma (FTC) is the second most common cancer of the thyroid and easily develops into distant metastasis. PD-L1 is known to be associated with the carcinogenesis and progression of thyroid carcinoma. Our study aimed to investigate the biological functions of PD-L1 and to identify miRNAs that were responsible for modulating the activity of PD-L1. Methods A total of 72 patients with FTC at The Second Affiliated Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Similar studies of other cancers have revealed an array of microRNAs that modulate these phenotypes through specific downstream targets, such as miR-331 and the downstream target BID, as well as miR-199 and the downstream target PD-L1, that have been demonstrated to mediate both proliferation and migration among thyroid cancers [ 26 , 27 ]. Similarly, miR-106 has been identified as mediating progression and invasion through HPGD and Smad7, while miR-296 may function through modulation of STAT3 among esophageal squamous cell carcinomas [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 95%
“…Similar studies of other cancers have revealed an array of microRNAs that modulate these phenotypes through specific downstream targets, such as miR-331 and the downstream target BID, as well as miR-199 and the downstream target PD-L1, that have been demonstrated to mediate both proliferation and migration among thyroid cancers [ 26 , 27 ]. Similarly, miR-106 has been identified as mediating progression and invasion through HPGD and Smad7, while miR-296 may function through modulation of STAT3 among esophageal squamous cell carcinomas [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, PD-L1 expression is positively correlated with Claudin-1 expression. Eventually, MiR-199a-5p plays a functional role in the progression and metastasis of FTC by regulating the expression of PD-L1 and Claudin-1 (p values < 0.05) [ 157 ].…”
Section: Micrornas: Bridging the Gap Between Gene Regulation Immune C...mentioning
confidence: 99%
“…The level of certain proteins and their metabolites is either increased or decreased, and their expression profile may be used for the diagnosis or risk stratification of cancers. There is a difference in the profile of proteins that are increased in the serum of patients who have thyroid nodules that may be used to assist in differentiating FTC from FA or PTC [ 201 ]. Immunohistochemistry on the FNAC specimen may be used in the diagnostic evaluation of indeterminate thyroid nodules [ 183 ].…”
Section: Multi-omics Of Follicular Carcinoma and Other Thyroid Tumorsmentioning
confidence: 99%
“…Adipocytes in the TME can promote tumor growth, progression, and metastasis through the secretion of adipokines). The differentiated profile of metabolites in the tumor itself, TME, and fluid in a patient with a thyroid nodule whose FNAC result is inconclusive may be used to differentiate FTC from FA or other follicular-patterned lesions [ 201 ]. The study of the change in levels of these molecules (metabolomics) is assessed using nuclear magnetic resonance spectrometry or mass spectrometry.…”
Section: Multi-omics Of Follicular Carcinoma and Other Thyroid Tumorsmentioning
confidence: 99%